2020
DOI: 10.1039/d0ma00728e
|View full text |Cite
|
Sign up to set email alerts
|

Versatile nature of anthanthrone based polymers as active multifunctional semiconductors for various organic electronic devices

Abstract: The versatility of anthanthrone-based materials in organic electronics is exploited by synthesizing four polymers, PANT, PANT-TBO, PANT-TBT, and PANT-TffBT. PANT represents the self-coupled homopolymer, while the other three are D-A...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In recent years, research in flexible electronics has unveiled rapid progress [1][2][3][4][5][6][7][8][9][10][11]. Great efforts have been demonstrated to study the solvent choices, controllable crystallization, charge carrier mobilities, and organic electronic device applications of solution-processed smallmolecular organic semiconductors, such as 6,13-bis(triisopropylsilylethynyl) pentacene (TIPS pentacene) [12][13][14][15][16][17], 2,7-dioctyl[1]benzothieno [3,2-b][1]benzothiophene (C 8 -BTBT) [18][19][20][21], 2,5di-(2-ethylhexyl)-3,6-bis(5''-n-hexyl-2,2',5',2'']terthiophen-5-yl)-pyrrolo [3,4-c]pyrrole-1,4-dione (SMDPPEH) [22][23][24] and 2,8-difluoro-5,11-bis(triethylsilylethynyl)anthradithiophene (diF-TES-ADT) [25][26][27][28].…”
Section: Recent Progress Of Flexible Electronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, research in flexible electronics has unveiled rapid progress [1][2][3][4][5][6][7][8][9][10][11]. Great efforts have been demonstrated to study the solvent choices, controllable crystallization, charge carrier mobilities, and organic electronic device applications of solution-processed smallmolecular organic semiconductors, such as 6,13-bis(triisopropylsilylethynyl) pentacene (TIPS pentacene) [12][13][14][15][16][17], 2,7-dioctyl[1]benzothieno [3,2-b][1]benzothiophene (C 8 -BTBT) [18][19][20][21], 2,5di-(2-ethylhexyl)-3,6-bis(5''-n-hexyl-2,2',5',2'']terthiophen-5-yl)-pyrrolo [3,4-c]pyrrole-1,4-dione (SMDPPEH) [22][23][24] and 2,8-difluoro-5,11-bis(triethylsilylethynyl)anthradithiophene (diF-TES-ADT) [25][26][27][28].…”
Section: Recent Progress Of Flexible Electronicsmentioning
confidence: 99%
“…In recent years, research on flexible electronics has witnessed rapid progress. 1–11 Great efforts have been made to study solvent choices, controllable crystallization, charge carrier mobilities, and organic electronic device applications of solution-processed small-molecular organic semiconductors, such as 6,13-bis(triisopropylsilylethynyl)pentacene (TIPS pentacene), 12–17 2,7-dioctyl[1]benzothieno[3,2- b ][1]benzothiophene (C 8 -BTBT), 18–21 2,5-di-(2-ethylhexyl)-3,6-bis(5′′- n -hexyl-2,2′,5′,2′′]terthiophen-5-yl)-pyrrolo[3,4- c ]pyrrole-1,4-dione (SMDPPEH) 22–24 and 2,8-difluoro-5,11-bis(triethylsilylethynyl)anthradithiophene (diF-TES-ADT). 25–28 For instance, based on the structural engineering of the organic semiconductor pentacene, the herringbone packing patterns in TIPS pentacene are interrupted by the attachment of the bulky side chains, which improves the solubility of TIPS pentacene in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3 In fact, many of them possess synthetic handles like halogens and ketone that allow easy chemical functionalization and modifications of their electronic properties. Recently, vat orange 3 (4,10dibromoanthanthrone) has been used as the starting material for several -conjugated molecules and polymers for multiple applications, including field-effect transistor, [4][5][6][7] light-emitting diodes, 8,9 aggregation-induced emission (AIE), 10 solar cells [11][12][13][14][15][16][17] and singlet fission. 18,19 This dye showed good versatility as it can be functionalized at the 4, 6, 10 and 12 positions to yield materials with a wide range of properties.…”
Section: Introductionmentioning
confidence: 99%
“…The OLED device fabricated with poly-TF through the spin-coating method showed a pure blue emission, demonstrating the huge potential of TF to construct emissive materials for OLEDs. Another building block we are interested in is the anthanthrone (ANT), which is a very promising building block in organic electronics because of its ultra-large fused-ring π structure [ 27 , 28 ]. In our group, we have developed ANT-based materials for various electronic devices, including perovskite solar cells, organic photovoltaic devices, thin film transistors, and chemical sensors [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another building block we are interested in is the anthanthrone (ANT), which is a very promising building block in organic electronics because of its ultra-large fused-ring π structure [ 27 , 28 ]. In our group, we have developed ANT-based materials for various electronic devices, including perovskite solar cells, organic photovoltaic devices, thin film transistors, and chemical sensors [ 27 , 29 ]. It is reported that the substitutions on different active sites of ANT also enable highly efficient blue-color OLEDs [ 30 ], prompting us to study ANT-based polymers for OLEDs.…”
Section: Introductionmentioning
confidence: 99%